2016
DOI: 10.1038/srep22889
|View full text |Cite
|
Sign up to set email alerts
|

Complement factor H binding of monomeric C-reactive protein downregulates proinflammatory activity and is impaired with at risk polymorphic CFH variants

Abstract: Inflammation and immune-mediated processes are pivotal to the pathogenic progression of age-related macular degeneration (AMD). Although plasma levels of C-reactive protein (CRP) have been shown to be associated with an increased risk for AMD, the pathophysiological importance of the prototypical acute-phase reactant in the etiology of the disease is unknown, and data regarding the exact role of CRP in ocular inflammation are limited. In this study, we provide mechanistic insight into how CRP contributes to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 56 publications
3
64
0
2
Order By: Relevance
“…In other studies it has been proposed that it is the monomeric (pro-inflammatory) rather than pentameric (anti-inflammatory) form of CRP that interacts with FH and, in this way, limits complement activation, increases phagocytosis of apoptotic cells and reduces the inflammatory response by macrophages [77]. Interestingly, it has been observed that the 402H variant of FH has reduced binding to monomeric CRP as compared to the 402Y allele, and, therefore, in this context, may have an impaired anti-inflammatory activity [64, 96, 97]. …”
Section: Other Ligands Of Factor Hmentioning
confidence: 99%
“…In other studies it has been proposed that it is the monomeric (pro-inflammatory) rather than pentameric (anti-inflammatory) form of CRP that interacts with FH and, in this way, limits complement activation, increases phagocytosis of apoptotic cells and reduces the inflammatory response by macrophages [77]. Interestingly, it has been observed that the 402H variant of FH has reduced binding to monomeric CRP as compared to the 402Y allele, and, therefore, in this context, may have an impaired anti-inflammatory activity [64, 96, 97]. …”
Section: Other Ligands Of Factor Hmentioning
confidence: 99%
“…CFH from AMD patients carrying the 'risk' His402 polymorphism display impaired binding to mCRP, and therefore pro-inflammatory effects of mCRP remain unrestrained, at least in vitro. 69 Whether this translates to disease or not requires validation but even so alone does not account for all the immune-related changes we observe in AMD.…”
Section: Understanding Uveitismentioning
confidence: 99%
“…Considering that FH binds to arterial proteoglycans deposits, 23 CRP 39 and fibromodulin, 40 and that cholesterol crystals activate complement, 41 increased FH levels in dyslipidemic CD might be a consequence of a stimulated FH secretion by adipocytes in an attempt to restrict complement driven damage during lipid metabolism dysregulation. Additionally, the FH His402 polymorphism displays impaired binding to mCRP, 42 although this was not evaluated in this study.…”
Section: Discussionmentioning
confidence: 91%